Improved (G′/G)-expansion method for the space and time fractional foam drainage and KdV equations - Akgul, Ali; Kilicman, Adem; Inc, Mustafa (Hindawi Publishing Corporation, 2013)
The fractional complex transformation is used to transform nonlinear partial differential equations to nonlinear ordinary differential equations. The improved (G′/G)-expansion method is suggested to solve the space and time fractional foam drainage and KdV equations. The obtained results show that the presented method is effective and appropriate for solving nonlinear fractional differential equations.